Historical Construction of Local Food System Transformations in Lebanon: Implications for the Local Food System - Mukahhal, Walid; Abebe, Gumataw Kifle; Bahn, Rachel A.; Martiniello, Giuliano (Frontiers in Sustainable Food Systems, 2022)
Food system transformations occur in a complex political, economic, social, and territorial landscape. The study provides a historical construction of global food regime changes and the adaptiveness, transformability, and resilience of the local food system in Lebanon, a Middle Eastern context. Lebanon offers a unique opportunity to understand the influence of global food regimes and geopolitics on agriculture, the local food system, and capital accumulation. After the 1975-1990 Lebanese Civil War, Lebanon experienced food retail transformation and international penetration through foreign investments. These alterations have several implications for society and the local food system: farming households' influence on agricultural policies and the political commitment to support the framing community decreased. The paper concludes that Lebanon's local food system transformation is a manifestation of geopolitical events and global food regime changes. This may have important implications and pave the way for a new food system that is based on the revitalization of agriculture and new forms of geoeconomic partnerships with regional actors.